Identification and optimization of a novel series of selective PIP5K inhibitors. (15th January 2022) - Andrews, David M.; Cartic, Sharon; Cosulich, Sabina; Divecha, Nullin; Faulder, Paul; Flemington, Vikki; Kern, Oliver; Kettle, Jason G.; MacDonald, Ellen; McKelvie, Jennifer; Pike, Kurt G.; Roberts, Bryan; et al.
Graphical abstract: Abstract: Phosphatidyl inositol (4, 5)-bisphosphate (PI(4, 5) P 2 ) plays several key roles in human biology and the lipid kinase that produces PI(4, 5) P 2, PIP5K, has been hypothesized to provide a potential therapeutic target of interest in the treatment of cancers. To better understand and explore the role of PIP5K in human cancers there remains an urgent need for potent and specific PIP5K inhibitor molecules. Following a high throughput screen of the AstraZeneca collection, a novel, moderately potent and selective inhibitor of PIP5K, 1, was discovered. Detailed exploration of the SAR for this novel scaffold resulted in the considerable optimization of both potency for PIP5K, and selectivity over the closely related kinase PI3Kα, as well as identifying several opportunities for the continued optimization of drug-like properties. As a result, several high quality in vitro tool compounds were identified (8, 20 and 25 ) that demonstrate the desired biochemical and cellular profiles required to aid better understanding of this complex area of biology.